Art - bridging communication and restoring self-confidence: (A sociological view) - Muhammad Saleh, Thanaa (Al-Adab Journal, 2019)
After 2003, the Iraqi demographic features changed with its social dimension, which includes all the cultural, economic and political dimensions. What justifies our reading of art from the outside as well as the inside. After art, like the West, has become a double-edged sword, and the desire is urgent to confront itself in: 1- deceiving and shading the masses as Adorno describes it, 2- class or class limitedness 3- "manipulating minds" as an expressive summary of Bourdieu's vision of the trilogy (individual - education - family) And its impact on artistic creativity or any field of life. 4- The negative view of art or the artist and considering art as a tool for fun, as Maan Khalil Omar expresses. And activating it educationally through primary schools, taking into account that art has characteristics and functions that are not negligible, whether psychologically or socially, after the repercussions of crises, whether international, local or individual, and their reflection on the personality. Especially since crises have produced categories (adolescent girls - bullies - etc. from categories that crises in primary schools make) that cannot be described as sick or deviant, because they are near or below disease or deviation, and the need is necessary to restrict these groups and work to help them overcome the causes that make them A victim of mental or nervous disease or deviation .... And I thought that art should be a type of human treatment that may contribute to the formation of a world for these people, and in turn this world may help those groups to reconsider their evaluation of themselves. After the desire for: 1- communication and 2- restoring self-confidence - a basis for measuring the normal personality of that category, given that these categories lack these two personality traits. And as Ernst Fischer says that the merging of (the ego) and (the we) is done through art, so he says (that art is the tool necessary to complete this integration of the individual and the group, as it represents the unlimited human ability to meet others and to exchange opinion and experience with them), and the researcher says Art is for everyone and for everyone because it is a human instinct that gives birth to us, and the surrounding environment has a role that cannot be underestimated, as a mechanism for the reproductive activation of the human instinct, and education is its basic tool. Assuming that the reality, from the researcher's point of view, will be dealt with according to the vision that adolescent girls or bullies have creative, unmotivated faculties and an urgent desire to stimulate them and employ those capabilities objectively - reconnect - and subjectively - restore self-confidence. Through the school and its educational mechanisms towards art. In the sociological perspective, he says, "We study to discipline," "Marxist, we study to change," and "Weberian, we study to understand and interpret." These insights are urgently needed in classical social theory. Which contemporary theory has contributed to its expansion as Bourdieu's theory of practice and its taking, the concept of habitus, and the field, essentials for explaining the duality of subject and object, as well as offering more concepts to help explain social phenomena. Like cultural capital, social capital, symbolic capital, paying great attention, as Badawi says, to reason and science. While stressing the importance of social upbringing, he is an educational family for his firm and inevitable belief in the importance of the dominant class in education and its role in curbing the individual abilities. Bourdieu emphasized the "relationship between artistic creativity and society," but he was also keen on interpreting art in light of what his approach served, while Adreno preceded him in proposing the "concept of creating culture", stressing the use of the data in language theory or sociology and history in the interpretation of art. .